Risk assessment of glacial debris flow on alpine highway under climate change: A case study of Aierkuran Gully along Karakoram Highway - Li, Ya-mei; Su, Li-jun; Zou, Qiang; Wei, Xue-li (Journal of mountain science, 2021)
Glacial debris flows (GDFs) often occur in alpine regions that are subject to rapid climate change, and pose a serious threat to road systems. However, the ways that climate change impacts GDF risks along road systems remain poorly understood. Aierkuran Gully, located in eastern Pamir along Karakoram Highway (KKH), is a hotspot for GDF activity and climate change, and was thus selected to investigate the GDF risk to road systems under climate change conditions. RegCM4.6 climate data for northwestern China were selected as climate projections during baseline (2011–2020) and future periods (2031–2040) under the Representative Concentration Pathway (RCP) 8.5. To reflect the coupling effect of rainfall and melt water that triggers GDF, a glacial hydrological model DETIM that considers both factors was applied to calculate the peak debris flow discharge. A FLO-2D model was calibrated based on high-quality data collected from a detailed field investigation and historical debris flow event. The FLO-2D model was used to simulate the debris flow depth and velocity during baseline and future periods under RCP8.5. The debris flow hazard was analyzed by integrating the maximum flow depth and momentum. Road structure vulnerability was further determined based on the economic value and susceptibility of hazard-affected objects. The GDF risk along KKH was assessed based on the GDF hazard and vulnerability analysis. Our results show that climate change would lead to amplified peak debris flow discharge, trigger higher-magnitude GDF, and induce more severe damage and threats to the road system. Compared with the baseline period, the debris flow damage risk for culverts and bridges would increase and the areas that inundate the road and pavement would expand. Our findings provide valuable insights for the development of mitigation strategies to adapt road systems to climate change, especially in alpine regions with highly active GDFs.